Influence of fear of COVID-19 on depression: The mediating effects of anxiety and the moderating effects of perceived social support and stress perception - Li, Xiaoyu; Yang, Pengcheng; Jiang, Yanju; Gao, Dongdong (Frontiers in Psychology, 2023)
To explore how fear of COVID-19 of female liberal arts undergraduates can directly and indirectly influence depression, with anxiety as a mediator and perceived social support and stress perception as moderates. From February to March 2020, 1196 valid data were collected online by questionnaire method. Fear of COVID-19 Questionnaire, the Patient Health Questionnaire9-Item Scale (PHQ-9), the Generalized Anxiety Disorder7-Item Scale (GAD-7), the Perceived Social Support Scale (PSSS) and the10-item Perceived Stress Scale（PSS-10）were used as the survey instrument, and the participants were female undergraduates from a liberal arts college of a Chinese university. Common method bias was assessed using Harman’s single-factor test in SPSS and confirmatory factor analysis in AMOS. The levels of participants’ anxiety, depression and perceived social support were described using frequency and percentage, Pearson Correlation test was used to measure the correlation between the variables. The PROCESS macro for SPSS (Model 1, Model 4 and Model 21) were applied to examine the mediating effect and moderating effect of the model. The results show that the fear of COVID-19 can positively influence depression, anxiety plays a mediating role between fear of COVID-19 and depression, perceived social support negatively moderates the relationship between fear of COVID-19 and anxiety, and stress perception positively moderates the relationship between anxiety and depression. These five variables can form a moderated mediating effect model. The moderating effect of perceived social support on mediating effect is greater than that of stress perception. The study reveals the mechanism of the relationship between fear of COVID-19 and depression, which is helpful to further understand the mediating role of anxiety and the moderating role of social support and stress perception during the COVID-19 period. The results suggest that reducing the fear of COVID-19, anxiety and stress perception and enhancing perceived social support are beneficial to reduce the level of depression in undergraduates.